Mental health nurses' views about antipsychotic medication side effects. Issue 6 (28th June 2016) - Stomski, N. J.; Morrison, P.; Meehan, T.
Accessible summary: What is known on the subject?: The only previous quantitative study that examined nurses' use of assessment tools to identify antipsychotic medication side effects found that about 25% of mental health nurses were using assessment tools. No previous studies have examined factors that influence the manner in which mental health nurses assess antipsychotic medication side effects. What this paper adds to existing knowledge?: One‐third of the respondents were not aware of any antipsychotic medication side‐effect assessment tool, and only one‐quarter were currently using an assessment tool. 'Service responsibility' was significantly associated with ongoing use of antipsychotic medication assessment tools, indicating that respondents with more positive attitudes to their service were more likely to continue using antipsychotic medication assessment tools. What are the implications for practice?: The low level of awareness and use of antipsychotic medication side‐effect assessment tools indicates that nursing educational institutions should incorporate more detail about these tools in course content, and emphasize in particular the benefits that result from the use of these tools in clinical practice. Service processes contributed significantly to the use of antipsychotic medication assessment tools, which indicates that managers need to foster workplace cultures that promote routine use of these tools. Abstract: Introduction: Limited evidence suggests that only a minority of mental health nurses regularly use standardized assessment tools to assess antipsychotic medication side effects, but the factors that contribute to the non‐routine use of these tools remain unknown. Aim: To examine Australian mental health nurses' awareness of, and attitudes towards, side‐effect assessment tools, and also identify factors the influence the use of these tools. Methods: A cross‐sectional survey was undertaken through distributing an online questionnaire via email to members of the Australian College of Mental Health Nurses. Completed questionnaires were received from 171 respondents. Linear regression was used to examine the relationship between the 'service responsibility' and 'personal confidence' scale scores, and awareness, previous use and ongoing use of antipsychotic medication assessment tools. Results: Only one‐quarter of the respondents (26.5%) were currently using an assessment tool. 'Service responsibility' was significantly associated with ongoing use of antipsychotic medication assessment tools ( Β = 3.26; 95% CI 0.83–5.69). 'Personal confidence' did not influence the ongoing use of assessment tools ( Β = −0.05; 95% CI −1.06–1.50). Implications for clinical practice: Stakeholders can incorporate 'service responsibility' processes to foster increased use of assessment tools, which may enhance the identification antipsychotic medication side effects and improve the quality of care for service users.